Kabardian public sum in political practices of local self-government in the Kabardian (Nalchik) district in the second half of the XIX – early XX centuries - Dmitry N. Prasolov (Кавказология, 2023)
Based on archival documents and materials of pre-revolutionary periodicals, examples of political use of the Kabardian public sum are examined. This financial institution was formed as a monetary fund, which was managed by the authorities of the Central Caucasus Line. court deputies were involved in its management, and later the drawing up of decisions on allocations from the public fund became the function of the congress of entrusted rural societies, whose decisions were approved by the crown regional or all-Caucasus superiors. Within the framework of the considered theme, allocations from the means of sum for maintenance of the activity of public officials, payment of expenses on participation of the Kabardian and Balkarian proxies in various public-political events, financing of various forms of political socialization and ideological maintenance of the subject political culture were revealed. At the expense of Sum funds, technological modernization of the communication capabilities of the district authorities and local self-government was carried out. The conclusion that in the practices of the congresses of confidants, Sum acted as a key financial resource through which the co-financing of regional political tasks was provided is substantiated. In the socio-state interaction organized by crown authorities and local self-government, first through the congresses of trusted rural societies, the political and cultural experience of Kabardinians and Balkars in organizing and improving the management of joint life within the framework of the Nalchik district expanded.